Evaluation and Comparison of Metabolic Disorders between Patients with Unilateral and Bilateral Staghorn Renal Stones - Mohammadi Sichani, Mehrdad; Jafarpisheh, Amir; Ghoreifi, Alireza (Urology Journal, 2019)
Purpose: Metabolic disorders are common in patients with staghorn renal stones. Aim of this study was to evaluate and compare the metabolic disorders in patients with unilateral and bilateral staghorn stones. Materials and Methods: In this cross sectional study, 78 patients who underwent percutaneous nephrolithotomy (PCNL) for staghorn renal stones were included. The urine volume, the level of calcium, oxalate, uric acid, phosphate, sodium, citrate, creatinine, and cystine from 24 hour urine collection as well as the serum levels of calcium, phosphorus, magnesium, creatinine, blood urea nitrogen (BUN), parathyroid hormone (PTH) and uric acid were recorded and compared among the two groups with unilateral and bilateral renal stones. Results: 56 patients (71.8%) had unilateral and 22 (28.2%) had bilateral renal stones. At least one abnormal metabolic factor was found in 32 (57.1%) and 15 (68.2%) patients with unilateral and bilateral renal stones, respectively (P = .044). Cystine urine levels and serum levels of BUN were higher in cases with bilateral compared to unilateral renal stones (36.4% vs. 12.5%, P = .025 and 27.3% vs. 1.8%, P = .002, respectively). Conclusion: Metabolic factors are strongly correlated with the formation of staghorn renal stones specially bilateral ones. In our study among different metabolic factors, cystine urine levels and serum levels of BUN were significantly higher in patients with bilateral renal stones. Proper metabolic assessments are recommended in patients with staghorn urolithiasis.